2020
DOI: 10.24990/injec.v6i1.365
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Adolescents’ Compliance on Covid-19 Prevention Protocols

Abstract: Introduction: Coronavirus disease (Covid-19) is an infectious disease that has become a global pandemic with 27 cases in Manggarai Regency. The adolescent as an age group with more asymptomatic hosts of the disease would be the super spreader of covid-19 to the other higher-risk age groups. The objective of this study is to identify the factors predicting adolescents’ compliance behavior toward Covid-19 prevention protocols. Methods: This study used quantitative descriptive method with a cross-sectional approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
3
2
0
3
Order By: Relevance
“…This is consistent with previous studies which stated that the majority of female secondary school students adopted better behavior and had a higher level of knowledge on hand hygiene and personal protection than their male counterparts (Guzek et al, 2020). This also includes mask-wearing and physical distancing during the pandemic (Ningsih et al, 2021). Nevertheless, in our study, boys reported more behaviors that increase the body's immune response compared to girls.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which stated that the majority of female secondary school students adopted better behavior and had a higher level of knowledge on hand hygiene and personal protection than their male counterparts (Guzek et al, 2020). This also includes mask-wearing and physical distancing during the pandemic (Ningsih et al, 2021). Nevertheless, in our study, boys reported more behaviors that increase the body's immune response compared to girls.…”
Section: Discussionsupporting
confidence: 92%
“…This research is also in line with research (Sari, et al, 2020)which stated that female respondents had good Covid-19 prevention behavior of 88.90%, while male respondents had good behavior to prevent Covid-19 transmission of only 76.88% (p value = 0.000). Other studies that are in line with the results of the research binary logistic regression test (Ningsih, Eka, & Danal, 2021)show a significant influence between gender, namely the female sex 1,941 is more influential than the female sex (95% CI: 0.898-4.195, p = 0.027).…”
Section: Gender Against Behavior Of Covid-19 Transmission Prevention ...supporting
confidence: 66%
“…In addition, good knowledge and perceptions about covid-19 also play a role in a better level of covid-19 prevention. [8,9,10,11] Overall, the majority of the levels of knowledge, preventive attitudes, and preventive actions of COVID-19 are good. These good knowledge supported by positive attitude and good practices are critical not only to prevent further infection, but more importantly in protecting their generation from the unknown long-term impact of Covid-19.…”
Section: Discussionmentioning
confidence: 98%